Treatment of Rosacea using acupuncture for improving the local skin microcirculation: A case report. Issue 34 (August 2018) - Gao, Yacen; Lin, Weipeng; Zhou, Sisi; Shi, Guoqi; He, Jun; Chen, Yongjun
Abstract: Rationale: Rosacea is an irritating disease that affects patients' health and life quality. The current treatments for rosacea have limited efficacy and are generally not satisfying most patients. This report presents a patient diagnosed with rosacea who was treated with acupuncture to a satisfactory effect. Laser Doppler was used to measure the local blood perfusion of the nose before, during, and after acupuncture treatment. The Dermatology Life Quality Index (DLQI) was used to measure the impact of rosacea on the quality of the patient's life. Patient concerns: A 52-year-old woman had been diagnosed with rosacea 18 months before this study. She had tried medical treatments in other hospitals with metronidazole cream, antifungal drugs, and steroidal ointments, but the effect was poor and limited. Diagnoses: In this study, the diagnosis of rosacea (stage I, subtype Erythematotelangiectatic) was made by a dermatologist according to physical examination). Interventions: The patient's treatment included a half-hour of acupuncture 3 times per week. Outcomes: The patient experienced significant improvements in the region around the nose after 3 sessions of acupuncture treatment within the first week and reported that there was no relapse for 6 months after acupuncture treatment. The perfusion of blood flow was redistributed during and after acupuncture treatment according to laser Doppler measurements. The patient's DLQI score substantially improved. The patient was generally satisfied with the acupuncture treatment. Lessons: The results suggested that acupuncture might be an alternative therapy for facial localized rosacea. As well, acupuncture may be effective in treating rosacea through redistributing micro-circulation of blood at the localized area of effect. The overall costs of the rosacea treatment may be reduced, provided that this therapy is demonstrated to be effective in future controlled studies.